THE EFFECT OF ERM, FIRM SIZE, LEVERAGE, PROFITABILITY AND DIVIDEND POLICY ON FIRM VALUE (EVIDENCE FROM FOOD & BEVERAGE SUB SECTOR COMPANIES LISTED IN IDX 2015-2019) - Irma Aprilyani; M. Th Heni Widyarti; Nurul Hamida (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
Enterprise risk management (ERM), firm size, leverage, profitability, and dividend policy is believed have an impact on firm value. However empirical evidence on thus impact is still considered scarce. The objectives of this study is to determine the effect of ERM, firm size, leverage, profitability, and dividend policy on firm value either simultaneously and partially. This study used purposive sampling technique. The samples used in this study is 14 companies listed and traded on the Indonesia Stock Exchange. The data analysis method used is multiple linier regression. The ERM variable in this study is measured with a dummy, Ln of total asset is used to measure the firm size. Debt to equity ratio used as a proxy of leverage, return on assets used as a proxy of profitability, dividend payout ratio as a proxy of dividend policy, then Tobin’s Q as a proxy of firm value. The results of this study indicate a simultaneous significant effect between the independent variables and firm value. Partial test shows that leverage and profitability have a significant positive effect on firm value. ERM & firm size have a negative coefficient and have no significant effect, while dividend policy has a positive coefficient but does not have a significant effect on firm value.